2007
DOI: 10.1248/bpb.30.27
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effects of Hydroxyl Radical Generation by Ga-Al-As Laser Irradiation on Mineralization Ability of Human Dental Pulp Cells

Abstract: The present study was conducted to investigate the effects of Ga-Al-As laser irradiation on the mineralization ability of human dental pulp (HDP) cells. HDP cells in vitro were irradiated once with a Ga-AL-As laser at 0.5 W for 500 s and at 1.0 W for 500 s in order to investigate free radicals as one mechanism for transmission of laser photochemical energy to cells. Production of the hydroxyl radical ( · OH) was measured using the ESR spintrapping method and was found to be increased by laser irradiation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 32 publications
4
42
0
5
Order By: Relevance
“…Histological studies have reported that hard tissue formation is enhanced as a reaction of dental pulp to laser light. 16,17 In the present study, the non-immediate effect of Low Intensity Laser, but gradual reduction in sensitivity over a period of 6 months can explain the biomodulation effect.…”
Section: Discussionmentioning
confidence: 50%
“…Histological studies have reported that hard tissue formation is enhanced as a reaction of dental pulp to laser light. 16,17 In the present study, the non-immediate effect of Low Intensity Laser, but gradual reduction in sensitivity over a period of 6 months can explain the biomodulation effect.…”
Section: Discussionmentioning
confidence: 50%
“…LPLI has been demonstrated to increase the level of intracellular ROS generation. 31 With LPLI treatment, light is absorbed by endogenous photosensitizers (porphyrins or cytochromes) that dominantly locate at plasma membrane, mitochondria or lysosomes. The photosensitizers' activation results in ROS (1O2, O-2 and H2O2) production.…”
Section: Discussionmentioning
confidence: 99%
“…The results of clinical studies concerning the various PBM effects have potential, even though they have not yet been clearly demonstrated (105,106). In a study examining the effects of Nd:YAG laser on blood flow in pulp tissue using laser Doppler flowmetry in mandibular canines from 13 human patients, a significant increase of blood flow in the dental pulp was noted in all laserirradiated (30 s at 120-mJ pulses at 10 pulses/s) teeth (105).…”
Section: Future Directionsmentioning
confidence: 99%
“…In a study examining the effects of Nd:YAG laser on blood flow in pulp tissue using laser Doppler flowmetry in mandibular canines from 13 human patients, a significant increase of blood flow in the dental pulp was noted in all laserirradiated (30 s at 120-mJ pulses at 10 pulses/s) teeth (105). Moreover, an in vitro study (106) reported that the mineralization of human dental pulp (HDP) cells is stimulated by laser irradiation. Several animal (74,75,85) and clinical (100) studies have reported favorable or potential formation of reparative dentin following laser therapy.…”
Section: Future Directionsmentioning
confidence: 99%